2019
DOI: 10.1039/c9sm00192a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the oscillatory wetting–dewetting motion of a volatile drop during the deposition of polymer on a solid substrate

Abstract: We employ a theoretical model to explain the wetting–dewetting motion of the contact line by incorporating opposing evaporation and Marangoni induced flows in the deposition process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Recently, Jabal et al observed a wetting−dewetting transition caused by the variation in surface tension near the CL as a result of the solute concentration. 52,53 This is in accordance with the above arguments.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Recently, Jabal et al observed a wetting−dewetting transition caused by the variation in surface tension near the CL as a result of the solute concentration. 52,53 This is in accordance with the above arguments.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…When the substrate was heated, fluid flowed outward the droplet due to high solvent evaporation rates at the edges. [30][31][32][33] In other words, the capillary flow carried the QDs to the droplet edge (Figure 2a(ii)), result-ing in an increased QD concentration at the droplet edge. As the heating process prolonged, more solvent was evaporated, resulting in the reduction of the contact angle between the droplet and the substrate as shown in Figure 2b-e.…”
Section: Resultsmentioning
confidence: 99%
“…where φ(r, t) is the particle volume fraction averaged by the film thickness, ρ l is the liquid density, and U ω is the fluid flow velocity in subdomain ω. The vapor flux density J(r, t) is determined using the Hertz-Knudsen formula [35,36,37,38,39,40]…”
Section: Model Equationsmentioning
confidence: 99%